Integrazioni Tecnologiche e Rilievo Archeologico - Il caso di Tindari - Angelini, Dario; Fasolo, Michele; Santarsiero, Domenico; Sfacteria, Marco (Archeomatica, 2017)
This work shows the first results of the metric survey, through the integrated use of a series of methodologies and techniques, of the fortifications of the city of Tyndaris. The features of these walls make it an interesting example of military architecture whose chronology is still a vexed question. The size and location of the structures, partly subject to superfetches that reach the modern age, together with the uneven condition of their conservation, have always made difficult to carry out an analytical survey of the monument in its entirety. The integrated use of a set of topographic survey technologies in a sample area of the monument has given promising results to date, in view of completing the relief of all the monument.